A study on the parameters affecting the properties of coated paper honeycomb - Abd Kadir, Nurdina; Aminanda, Yulfian; Shaik Dawood, Mohd. Sultan Ibrahim; Mohktar, Hanan (IOP Publishing, 2017)
In this study, three parameters, namely the density of Kraft paper, the thickness of cell wall and the cell size of honeycomb were evaluated. A statistical analysis was performed to investigate the effect of the parameters on the specific compression strength(SCS) and specific energy absorption (SEA) of Kraft paper honeycomb. Based on the design of experiment, 27 configuration of Kraft paper honeycomb with different cell sizes (10mm,15mm,20mm), thicknesses of cell wall (1ply, 2ply, 3ply) and paper densities (80gsm,120gsm,175gsm) are subjected to quasi static compression loading. An analysis of variance (ANOVA) was used to examine the effect of each parameters and to obtain the optimum configuration of Kraft paper honeycomb. As a result, the thickness of cell wall shows as the most prominent parameter for specific energy absorption and specific compression strength. Meanwhile, the Kraft paper honeycomb with density 175gsm, 3 ply thickness of paper and 10mm cell size of honeycomb shows the optimum configuration with 724.80 J/kg of SEA and 9.35 MPa/kg of SCS